Leadership humility and managing a multicultural workforce. (1st May 2020) - Hutt, Camille; Gopalakrishnan, Shanthi
Abstract : Purpose: The purpose of this paper is to understand how CEO Joseph Abraham of Commercial Bank, Qatar, has shaped the culture of the bank and driven increased success during his tenure there. This is one of a series of interview-based studies that are focused on South Asian CEOs, with the goal of better understanding their management style in a multinational context. This short paper explores how leadership style can impact the development of workplace culture among a multinational workforce to build a collaborative, innovative and high-performing organization. Design/methodology/approach: This paper uses primary interviews and supplements the analyses with secondary data sources and published research on leadership, organizational identity, culture and organizational ambidexterity. Findings: The study found that cultural values and learned behaviors impact one's leadership and vision. In this instance, the CEO's leadership style demonstrated humility, an appreciation of diverse national cultures, and an ability to create organizational identity and cultivate a culture of ambidexterity, providing comfort to the organization in dynamically opposite contexts. All of these leadership features have enabled the organization to become more adaptive and perform better. Originality/value: The narrative provides a glimpse of leadership humility and the implementation of those ideals in the workplace. The global experience of this South Asia-raised CEO provides an insider's view to decision-making and helps us understand how family, cultural background, and diverse work experience shape leadership behavior and culture in a multinational context.